Testing methods for shear strength of bond line between concrete and different types of engineered wood. (October 2020) - Fu, Qiuni; Yan, Libo; Kasal, Bohumil
Abstract: This paper identified a reliable testing method for determining the shear strength of bond lines between concrete and engineered wood. The identification was carried out based on analytical derivations and experimental tests on concrete (compressive strength of 24.8 MPa) and engineered wood composite connections glued by two types of epoxy. Forty specimens were tested under two commonly used test setups, i.e. 20 double-shear tests on timber-concrete composite specimens with a bond length of 50 mm and another 20 compression-shear tests on specimens with a bond length of 300 mm. The result analysis showed that there was no significant statistical difference between the shear strength of the bond lines (around 2.3 MPa) as well as between the failure modes obtained (dominated by concrete failure), regardless of the considered bond lengths and adhesive types investigated. The analysis used a quasi-non-linear fracture mechanics model, considering the boundary conditions of the tests. The analytical model revealed that the ultimate shear stress is approximately uniformly distributed both in the double-shear and in the compression-shear tests, so the spatially averaged shear stress value can approximate the critical shear stress of the bond line with sufficient accuracy. However, if the failure occurred in the wood or the strength of the concrete was higher, the shear stress distribution at ultimate load in the compression-shear tests with a bond length of 300 mm would not be uniform. The maximum shear stress value, which is significantly larger than the average one, occurred at the fixed (or supporting) end of the bond line. Even so, in the shear tests with a bond length of 50 mm, the average ultimate shear stress value was still close to the shear strength with a difference smaller than 5%. Hence, a bond length of 50 mm is recommended for determining the shear strength of a bond line between normal strength concrete and engineered wood when using a push-out shear test setup.